School bag load and its effect on Erector spinae muscle and low back pain among primary school children in Malaysia - Mohd Tamrin, Shamsul Bahri; Lim, Poh Ai; Hamzah, Azlan; Abdullah , Mohd Rotpi; Hanafi, Siti Sahartini (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2005)
A cross sectional study was conducted to determine and evaluate the effects of school bag load on electromyography (EMG) activity of the erector spinae muscle. Methods: Eighty four primary school children were selected from two national medium primary schools in Seri Kembangan, 42 from primary two (P2) and 42 from primary five (P5), aged 8 and 11 respectively. Data were collected through interviews, anthropometrics measurements, the weight of schoolbag load and surface electromyography (SEMG) of the erector spinae using muscle tester ME20000P. Surface Ag-AgCI electrodes were used to measure: unloaded standing and walking, and loaded standing and walking. Results: The study revealed that erector spinae was found to be more efficient in loaded standing probably due to other trunk muscle co-activity compared to unloaded standing (p<0.05). However, the erector spinae was less efficient when loads were carried on the back while walking, compared to unloaded walking. When the schoolbag was carried over both shoulders, forces generated by the erector spinae were reduced and resulted In more efficient use of the erector spinae compared to other asymmetrical carrying (p<0.05). conclusion: bending slightly forward when carrying schoolbag was found to reduce the forces generated by the erector spinae compared to normal sagittal posture (p<0.05), however no significant difference was found between the different frontal posture. A significant inverse relationship (p<0.01) between the weight of schoolbag load and the average electromyography (AEMG), showed that the significance of the erector spinae muscle co-activity. The study also revealed that apart from age of school children, family history of back pain, exposure to environmental tobacco smoke (ETS), weight of the schoolbag and method of carrying schoolbag also play important role as risk factors for back pain.